MARSHALL MCLUHAN AND THE APPEARANCE OF A NEW REALITY - Treviño, Pedro (HUMANITAS DIGITAL, 2021)
It is my belief that this statement should remain as an achievement in the perception of a new era as it has unfolded before us in the tangible world of art, In order to set a basis from which I will draw concepts to account for Faulkner's pattern of narration in As I Lay Dying, the comprehension of the twentieth century concepts of time and space are necessary. I believe that the observations of Dr. Marshall Mcluhan about the boundries of a "mechanical age" -as he names a period of time that has an uncertain genesis three thousand years ago and a definite end- with and "electric age", exemplify the change in the conceptualization of time and space which is so basic for our perception of reality. In the quote above, the key words are "mechanical" and "electric". The first term points to the description of the behavior of an object commonly called "the machine".